2022
DOI: 10.1039/d1ra07171h
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial interaction study of EDTA with the defect structure of Fe3−δO4 passive film in an aggressive alkaline medium based on the lattice theory of point defects

Abstract: Despite extensive research on the matter of corrosion inhibition efficiency, the interactions between the defect structure of the passive layer and the inhibitor molecules still remain poorly understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Published by the Royal Society of Chemistry that the absorbed medium to the coating, which comprises corrosive agents such as Cl À ions, could eventually reach the surface and once again trigger the metal dissolution reactions on the surface. 45 Hence, it is important to have a contingency plan, when the polymerization reaction of linseed oil and a physical barrier layer are not enough for guarantying the corrosion protection. Therefore, presence of the SDS molecules on the metal surface as the second corrosion inhibition mechanism is necessary.…”
Section: Smart Anti-corrosive Performancementioning
confidence: 99%
“…Published by the Royal Society of Chemistry that the absorbed medium to the coating, which comprises corrosive agents such as Cl À ions, could eventually reach the surface and once again trigger the metal dissolution reactions on the surface. 45 Hence, it is important to have a contingency plan, when the polymerization reaction of linseed oil and a physical barrier layer are not enough for guarantying the corrosion protection. Therefore, presence of the SDS molecules on the metal surface as the second corrosion inhibition mechanism is necessary.…”
Section: Smart Anti-corrosive Performancementioning
confidence: 99%
“…And the mechanism of ethylenediamine-tetraacetic acid was investigated. Both the EIS results (83%) and the potentiodynamic test (85%) results indicated that ethylenediamine-tetraacetic acid exhibited the best corrosion protection at 0.05 M [14]. Furthermore, Teymouri et al analyzed four carboxylate derivatives in simulated concrete pore solutions with 0.5 M NaCl for comparative purposes, and the test results showed that Trisodium Citrate (Cit) performed the highest corrosion inhibition at 0.1 M (91%) [15].…”
Section: Introductionmentioning
confidence: 99%